Computing concepts : - Haag, Stephen (McGraw-Hill Technology Education, 2004)
This exciting, new first edition concepts text emphasizes all that is current, cutting-edge, and interesting to students in the introductory course. Focusing specifically on users, consumers and purchasers of technology, this text provides a no-nonsense coverage of the absolute essentials for using technology in today¿s wired world. The I-Series offers excellent coverage on the basics, as well as extensive information on building a Web site, E-Commerce, implications of technological advances, maintaining a computer system, buying your first PC, and more. Each chapter also contains coverage of security, ethics, and privacy and an introduction to the web-based Life Long Learning modules.